A case study of waqf lands in Selangor: a proposed model for agribusiness / Norfaridah Ali Azizan - Ali Azizan, Norfaridah (2021)
This study explores the potential of the waqf lands in Selangor to be revitalised for agribusiness activities. The latest survey in 2018 shows that 87% of Malaysia's waqf lands are considered underutilised, which is a loss to the ummah, country, and the endower. Therefore, a pragmatic approach is needed to be developed and implemented so that the underutilised waqf lands can be transformed. Selangor is unique because it is among the most significant states in Malaysia, blessed with fertile lands. Likewise, the issues that affect waqf lands in Malaysia are also faced in Selangor, and the underutilised waqf lands in the state are too high. Agribusiness is suggested because this study viewed it as a pragmatic solution to address the problems of waqf lands and at the same time to assist the government in achieving the food security level for the country and to some extent, to lift the B40 economic situation. This study employed qualitative methods by interviewing nine key informants who are experts in their fields comprising Shariah experts, waqf management, agriculture authority, farmer and government agencies. They have discussed several pertinent issues such as Shariah requirements, legal consideration, financial constraints, location and size of the waqf lands, expertise to develop the waqf lands, the agreement's scope, and the responsible party to lead the initiative. Limitations are also being highlighted in the study, so readers will understand the research's whole discussion and the mitigation and explanation to address the limitations. At the end of the study, one model is proposed for agribusiness on the waqf lands: the Waqf Trustee-Anchor Company - Community Farmers Model, validated by the key informants.